DAMPAK DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DI UNIVERSITAS NUSANTARA PGRI KEDIRI - Dodi Kusuma Hadi Soedjoko (Cakrawala Management Business Journal, 2019)
Human resources play an important role in every organization or institution. But there was a decrease in employee performance at Nusantara PGRI Kediri University recently, this case becomes concideration to conduct this research. The purpose of this study is to determine the effect of work dicipline and compensation on the employee’s performance at Nusantara PGRI Kediri University. The approach of this study is descriptive quantitative. The sample in this study used all populations as a sample consisting of 73 employees. The technique of collecting data used a questionnaire with a Likert scale that contains of questions related to work discipline, compensation and employee performance. The data analysis technique used multiple linear regression which was processed using the SPSS program to measure the effect of work dicipline and compensation on employee’s performance. The results of hypothesis testing showed that partially, there was a significant effect of work discipline on employee performance and there was also significant effect of compensation on employee performance at Universitas Nusantara PGRI Kediri. While the results of simultaneous hypothesis testing proved that work discipline and compensation give significant effect for employee performance. It can be seen that coefficient dtermination value (R Square) was 0.676. Thus, it can be interpreted that work dicipline and compensation can effect on employee’s performance 67.6% while the remaining 32.4% was effected by other variables outside of this study.